Entre a proeza e a bobagem: uma análise sociológica sobre o palhaço e o circo - Ramos, Luís Eduardo Santos de Oliveira (2016)
This work search, through historical and sociological aspects, to understand the performance and the social function of the clown starting from its origins in the popular comic culture, through its incorporation into the modern circus to the way in which it presents today in various fields artistic, but more specifically in Brazilian circuses. Seeking to analyze own elements of clown and clowning art but also of circus art and circus as leisure and sociability, the sociological view build a history of the development of the clown as a character of the Brazilian and global popular culture through elements like laughter and its transformations and possibilities, the civilizing process and the control of emotions, leisure spaces and multiple possible artistic manifestations in which the clown is inserted. For better understanding of this discussion, addressed sociological theories will be related to my field experience which consists in interviews, observation shows and cohabitation held with clowns and other circus performers.